Recent Advances in Understanding the Role of Growth Regulators in Plant Growth and Development in Vitro - II. Non-Conventional Growth Regulators - Kalia, Rajwant K.; Singh, Rohtas; Kalia, Sanjay; Sharma, S. K.; Kumar, suresh (Indian Forester, 2016)
A diverse array of growth regulators interact at the cellular level to produce physiological and morphological effects on plant growth, morphology and yield. The five conventional growth regulators viz. auxins, cytokinins, gibberellins, abscisic acid and ethylene are being used in plant cell, tissue and organ cultures for decades, while many of them, like non-purine cytokinins, polyamines, jasmonates, brassinosteroids, oligosaccharides, sterols, phosphoinositosides, salicylic acid and systemins, have recently been discovered and tested for their effects in vitro. However, many have not yet been examined for their effects on in vitro growth and development of plants. In this review, we attempted to summarize the progress that has been made over the past two decades towards understanding the role of non conventional PGRs in plant growth and development.